Structural characterization of aminoglycoside 4′‐O‐adenylyltransferase ANT(4′)‐IIb from Pseudomonas aeruginosa. (29th January 2020) - Semper, Cameron; Stogios, Peter; Meziane‐Cherif, Djalal; Evdokimova, Elena; Courvalin, Patrice; Savchenko, Alexei
Abstract: Aminoglycosides were one of the first classes of broad‐spectrum antibacterial drugs clinically used to effectively combat infections. The rise of resistance to these drugs, mediated by enzymatic modification, has since compromised their utility as a treatment option, prompting intensive research into the molecular function of resistance enzymes. Here, we report the crystal structure of aminoglycoside nucleotidyltransferase ANT(4′)‐IIb in apo and tobramycin‐bound forms at a resolution of 1.6 and 2.15 Å, respectively. ANT(4′)‐IIb was discovered in the opportunistic pathogen Pseudomonas aeruginosa and conferred resistance to amikacin and tobramycin. Analysis of the ANT(4′)‐IIb structures revealed a two‐domain organization featuring a mixed β‐sheet and an α‐helical bundle. ANT(4′)‐IIb monomers form a dimer required for its enzymatic activity, as coordination of the aminoglycoside substrate relies on residues contributed by both monomers. Despite harbouring appreciable primary sequence diversity compared to previously characterized homologues, the ANT(4′)‐IIb structure demonstrates a surprising level of structural conservation highlighting the high plasticity of this general protein fold. Site‐directed mutagenesis of active site residues and kinetic analysis provides support for a catalytic mechanism similar to those of other nucleotidyltransferases. Using the molecular insights provided into this ANT(4′)‐IIb‐represented enzymatic group, we provide a hypothesis for the potential evolutionary origin of these aminoglycoside resistance determinants. Abstract : PDB Codes: 4EBJ, 4EBK